TUTORIAL PEMBELAJARAN DALAM MEMBUAT PERBEDAAN GAYA GAMBAR KARAKTER KARTUN DAN ANIME - Nurul Fadhillah (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2022)
Cartoons are television shows in the form of moving images that were discovered in 1883, as the times progressed, cartoons evolved not only in the entertainment world but also in the world of marketing, this attracted illustrators to create something unique to attract people's attention, from the storyline to the characters. Characters are important extras in film production, especially in animation to clarify the information that will be conveyed in the film. The more characters that are created, the more drawing styles are produced, even every artist has their own drawing style. For this reason, the world of drawing is starting to learn techniques on how to draw, to create something unique but proportional, one of which is drawing designs character. This article discusses the steps in creating and making cartoon and anime characters.